Harnessing pluralism for better health in Bangladesh - Ahmed, Syed Masud; Evans, Timothy G; Standing, Hilary; Mahmud, Simeen (© 2013 The Lancet, 2017)
This review was published in The Lancet [© 2013 The Lancet] and the definite version is available at: http://www.thelancet.com/journals/lancet/article/PIIS0140-6736(13)62147-9/abstract?rss=yes